PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS XII SMA NEGERI 2 PAYAKUMBUH - Utami, Puti Maharani (Departemen Matematika, 2025)
Students' ability to express mathematical concepts through the use of mathematical symbols and language is intrinsic to mathematics education, which in turn relates to mathematical communication. Class XII at SMA Negeri 2 Payakumbuh is still at a low level in this regard. The Think-Talk-Write (TTW) cooperative model offers a potential approach to overcome this problem. Compared to a conventional model, this learning model was tested to determine whether it could improve the ability to express mathematical concepts. This study used a quasi-experimental postest only control group design. The participants in this study were class XII F 9 and XII F 1 SMA Negeri 2 Payakumbuh. Based on the research results, the TTW model class has a higher class average than the conventional model class. Therefore, the TTW model outperforms the conventional model, as evidenced by the P-value <α.Keywords– Mathematical Communication Skills, Think Talk Write Model, Conventional Learning Model